Otosklerosis - Kurnia Fithrananda; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Otosclerosis is a hearing disorder with an abnormal condition of the process of remodelling the hearing bones that most often affects the stapes bone. This disease affects women more often than men by showing symptoms of decreased hearing, tinnitus, and vertigo. The ethology and pathophysiology of this disease are still controversial and unclear. However, there are several factors like infection, heredity, anatomy, and pregnancy that are said to be associated with this disease. Diagnostic enforcement of this disease is carried out by means of a CT Scan accompanied by various ear physical examinations. Until now, surgery and hearing aids are still considered the best treatment compared to administering drugs. The prognosis of this disease is said to be good, but there is still the possibility of recurrent conductive hearing loss.